2008
DOI: 10.1007/s10683-008-9208-2
|View full text |Cite
|
Sign up to set email alerts
|

Would I lie to you? On social preferences and lying aversion

Abstract: This paper reinterprets the evidence on lying or deception presented in Gneezy (2005, American Economic Review ). We show that Gneezy's data are consistent with the simple hypothesis that people are one of two kinds: either a person will never lie, or a person will lie whenever she prefers the outcome obtained by lying over the outcome obtained by telling the truth. This implies that so long as lying induces a preferred outcome over truth-telling, a person's decision of whether to lie may be completely insensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
163
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(182 citation statements)
references
References 12 publications
17
163
1
Order By: Relevance
“…Our results also help in testing a recent explanation of Gneezy's (2005) result offered by Hurkens and Kartik (2009). They offer an explanation that is a special case of the Gneezy (2005) one.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Our results also help in testing a recent explanation of Gneezy's (2005) result offered by Hurkens and Kartik (2009). They offer an explanation that is a special case of the Gneezy (2005) one.…”
Section: Resultssupporting
confidence: 74%
“…7 To test their hypothesis, one needs to find a design in which social preferences work in the same way, and hence only the cost of lying is relevant. As noted, Gneezy's (2005) or Hurkens and Kartik's (2009) design cannot test this; our design can. In particular, inequity models, or any other model of social preferences we are aware of, would predict that a person with no lying costs in treatment T 10 10 strictly prefers 30 30 over 20 20 , and one in T 10 0 strictly prefers 30 20 over 20 20 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, Gneezy (2005) studied the extent to which a laboratory participant with private information will lie to an uninformed participant 6 about which of two possible actions is more profitable. He found that people are sensitive to both their potential gains from a lie and to their counterparts' potential losses (see also Croson 2005;Hurkens and Kartik, 2009;Sutter, 2009;Gibson, et al, forthcoming;Erat and Gneezy, forthcoming). Recent research also explores the conditions under which individuals lie about the outcome of a random process, such as a die roll, to gain more money from an experimenter (Gino and Ariely, 2012;Shalvi, et al, 2011;Fiscbacher and Heusi, 2008).…”
Section: Relevant Literature and Hypothesesmentioning
confidence: 99%
“…Our findings provide new evidence for the existence of moral individuals that reject economic incentives to deceive (Hurkens & Kartik, 2009;Gneezy et al, 2013). Furthermore, we provide evidence that only a minority of investors is overly optimistic about the proportion of moral individuals in the economy.…”
Section: Introductionmentioning
confidence: 51%